The Fund's Income Position for FY 2008 : Midyear Review. (Policy Papers; Policy Paper, 2007)
This paper provides the basis for the Executive Board's midyear review of the Fund's income position based on developments in the first half of FY 2008. Under Rule I-6(4) of the Fund's Rules and Regulations, the Executive Board should consider whether the margin over the SDR interest rate used to calculate the rate of charge as determined at the beginning of the year should be changed in light of the actual income position for the first six months.